DAMPAK PROGRAM TERAPI RUMATAN METADON (PTRM) TERHADAP PASIEN PTRM DI SATELIT PELAYANAN PTRM PROVINSI DIY - qosim, julaeha (Universitas 17 Agustus 1945 Jakarta, 2016)
Background: Methadone Maintenance Treatment Program (MMTP) is one of the harm reduction program due to injecting drug use. The purpose of MMTP is replacing the use of narcotics (heroin) injection, was replaced with the use of oral methadone. MMTP expected to reduce drug use, risk behavior, crime, and increase productivity, housing conditions, and family support for injecting drug users (IDUs). MMTP in Yogyakarta has been implemented since 2006. Currently have been provided four MMTP satellite services are: Grhasia hospital, Gedongtengen primary health care (PHC), Umbulharjo I PHC and Banguntapan II PHC. As of November 2012 there were 39 actively registered patients (35 males, 4 females). Thirty-two patients voluntarily participated in this study. Objective: To determine the impact of MMTP on patients, including a reduction in drug use, risk behavior, crime, and increase productivity, housing conditions, and family support in the MMTP satellite services Yogyakarta. Method: Descriptive research with case study design and cross-sectional approach. This research conducted in October - December 2012. Subjects were 32 MMTP active patients. The independent variable is implementation of MMTP services and dependent variable is the impact of MMTP. The research instruments use questionnaires and interview guides. The data source are patient’s medical record, MMTP active patients, and MMTP teams (physicians, nurses, and pharmacists). Analysis of descriptive data in the form of percentage achievement of MMTP impacts on patients and pearson correlation analysis to determine the relationship between MMTP services with the impact of MMTP on patients. Result: thirty-two (100%) patients had been decrease in their criminal behaviour since admission to the MMTP. Seventeen (53%) patients they were not using alcohol and/or drug since their admission in the MMTP. The analysis result of Pearson correlation was found significance level of 0,001 (< 0,05). With relationship value of 0,588. There was a significant positive relationship between MMTP services with the impact of MMTP on patients. Conclusion: MMTP is useful in harm reduction due to injecting drug use. to improve counseling services in MMTP, MMTP teams should make scheduling of counseling time.